Pengaturan Justice Collaborator Dalam Tindak Pidana Narkotika Di Indonesia Dan Amerika Serikat - Nasrullah Umar Harahap; Evi Deliana; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The issue regarding the justice collaborator is a complex and interesting issue to be discussed in aconception or legilacy. Is a justice collaborator an offender or not a criminal offender, or is a special awardor protection and punishment needed given the very need for the role of justice collaborator in disclosing anextraordinary organized crime such as a narcotics crime. Law enforcers often encounter a deadlock todecide cases involving a justice collaborator because there is no adequate legal instrument to facilitatelegal guarantees to be obtained. The purpose of this paper is: first, the knowledge of justice collaboratorarrangements in narcotics crimes in Indonesia and the United States. Second, knowing the urgency ofjustice collaborator arrangements in narcotics crimes in Indonesia. Third, reviewing, encouraging andproviding input to be born an ideal idea of a justice collaborator arrangement in narcotics crime inIndonesia.This type of research used in legal research is a normative juridical method. Therefore, a qualitativemeasure of analysis is used which relies on the substance with data in drawing conclusions. In drawingconclusions, the writer uses deductive thinking method, which is a way of thinking that draws a conclusionfrom a statement or general proposition into a statement or case of a special nature.From the results of research and discussion it can be concluded that, First, regulation of justicecollaborators in narcotics crimes in Indonesia is still inadequate, especially in the aspect of institutionsauthorized to provide protection to justice collaborator. Second, the urgency of legal protection againstjustice collaborators in considering weighing Law Number 13 Year 2006 in conjunction with Law Number31 Year 2014 concerning Protection of Witnesses and Victims explained that guarantees of protectionagainst witnesses and victims have an important role in the criminal justice process so that with witnesstestimony and victims given freely from fear and threats can reveal a crime. In the provisions of the nextpoint it is explained that in order to disclose an overall attempt at a criminal offense, especially anorganized transnational crime, it is also necessary to protect witnesses, reporters and experts. Third, theidea of regulating a justice collaborator in the future of narcotics crimes in Indonesia (ius constituendum) isoriented to affirmation of the protection institution and the concept of a restorative justice approach.Keywords: Justice Collaborator-Narcotics Crime